(untitled) (International Journal of Creative Future and Heritage (TENIAT), 2019)
Kostum tradisional telah menduduki tempat yang terkenal di dunia, merentasi kawasan geografi dan keadaan iklim, sejak zaman purba. Walau bagaimanapun, terdapat kebimbangan dari pertindihan pakaian moden yang membawa kepada kepupusan pakaian tradisional. Di Yemen, banyak pakaian tradisional sudah hilang. Ini adalah penyataan masalah dalam kajian ini kerana kurangnya kajian dalam bidang pakaian tradisional dan perang di Yaman. Pemeliharaan, kebangkitan semula, dan kajian pakaian tradisional adalah perlu untuk memberikan panduan kepada ketukangan yang baik di Yaman. Kajian ini direka bentuk untuk merawat kostum tradisional di banyak tempat di Yemen. Kajian ini mengambil pendekatan kualitatif dengan pergi ke lapangan, membuat wawancara dan menghubungi orang lama untuk mengumpulkan maklumat mengenai pakaian tradisional dalam bentuk gambar di banyak tempat di Yemen dan menyusun koleksi foto ini menjadi inspirasi untuk generasi dan pereka fesyen masa depan. Traditional costumes have occupied a prominent place in the world, across geographic regions and climatic conditions, since ancient times. However, there is concern from the overlapping of modern clothing that lead to the disappearance of traditional clothing. In Yemen, a lot of traditional costumes already disappeared. This is the statement of problem in this study due to the lack of studies in the area of Yemeni traditional clothing and war in Yemen. The preservation, revival, and study of traditional clothing are necessary to provide a guide to good craftsmanship in Yemen and shaping the future of this industry. The study was designed on the sustenance of traditional costumes in many localities in Yemen. This study conducted through a qualitative approach by going to the field, conduct interviews and contacting old people in order to collect information regarding traditional costumes in form of photograph pictures in many localities in Yemen and sorted these photographs to become the inspiration for future generations and designers